2007
DOI: 10.17221/1886-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality and tissue fatty acid profiles in rabbits fed diets supplemented with conjugated linoleic acid

Abstract: In this study the deposition of dietary CLA isomers in loin and hindleg meat, liver and fat, and the influence on performance and fatty acid (FA) profile were investigated in growing rabbits. CLA was supplied as synthetically produced oil at 5 and 10 g/kg diet for the whole fattening period (six weeks) or three weeks before the slaughter. CLA had no or limited effect on feed intake, growth, carcass traits and composition of meat. Treatment with CLA increased the proportion of saturated FA at the expense of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
3
7
1
Order By: Relevance
“…The saturated fatty acid (SFA) content at 37.5% with a PUFA: SFA ratio at 1.06 emphasized qualitative and dietetic properties of rabbit meat. The results on fatty acid profile are in line with the earlier reported values (Jorge et al 2005;Marounek et al 2007). Nonetheless, the chemical composition and fatty acid profile fell within the normal range for rabbit meat (Zotte & Szendrő 2011).…”
Section: Resultssupporting
confidence: 93%
“…The saturated fatty acid (SFA) content at 37.5% with a PUFA: SFA ratio at 1.06 emphasized qualitative and dietetic properties of rabbit meat. The results on fatty acid profile are in line with the earlier reported values (Jorge et al 2005;Marounek et al 2007). Nonetheless, the chemical composition and fatty acid profile fell within the normal range for rabbit meat (Zotte & Szendrő 2011).…”
Section: Resultssupporting
confidence: 93%
“…This is in contrast to Peiretti et al (2007) and Lazzaroni et al (2009), which found more palmitic acid in the same depot. The values of oleic, linoleic and palmitic acid in this study are also different from results obtained by Marounek et al (2007) for Hyplus rabbits.…”
Section: Discussioncontrasting
confidence: 99%
“…The FA profiles of meat and fat can be effectively modified, when the rabbits are fed different dietary supplements. Enrichment of rations with oils derived from soybean, sunflower, rapeseed (Cobos et al, 1993), linseed (Kouba et al, 2008), camelina (Peiretti et al, 2007), sage (Peiretti & Meineri, 2008), whole white lupin seeds (Volek & Marounek, 2011), fat-soluble vitamins (Gondret et al, 1998;Dal Bosco et al, 2004) and conjugated linoleic acid (Marounek et al, 2007), results in an increased intake of polyunsaturated FAs. A similar positive correlation between the amount of dietary n-3 PUFA intake and monounsaturated fatty acids (MUFA) content of adipose tissue has been established in lambs (Nürn-berg, et al, 1998;Banskalieva et al, 2000), steers (French et al, 2000), pigs (Doichev, 2009) and humans (London et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Independent of the tissue, pigs fed CLA exhibited higher levels of saturated fatty acids (SFA), and lower levels of monounsaturated fatty acids (MUFA) than pigs fed lard (Bee et al 2001). The shift towards higher deposition of SFA and lower deposition of MUFA was observed also in lipids of other animal species: broiler chicks (Simon et al 2000), rabbits (Marounek et al 2007), and calves (Marounek et al 2008). Modification of the FA profile has attracted attention as meat containing less UFA and more SFA may be less prone to lipid oxidation.…”
mentioning
confidence: 93%